One perfect lie [large type] - Scottoline, Lisa (Thorndike Press, a part of Gale, Cengage Learning, 2017)
An emotional thriller and a suburban crime story that will keep listeners guessing until the end. On the surface, it tells the tale of the struggling single mother of a high-school pitcher, a shy kid so athletically talented that he's being recruited for a full-ride scholarship to a Division I college, with a future in major-league baseball. But the mother fears that she's losing her grip on her son because he's being lured down a darker path by one of his teammates, a secretly disturbed young man from an affluent family, whose excellent grades and fun-loving manner conceal his violent criminal plans. Add a handsome stranger who comes to town and infiltrates the high school, posing as a teacher but with a hidden agenda all his own.